Financial strategies for long-term success in women-owned small businesses - Melissa Renee Dyer (The Journal of Entrepreneurial Finance (JEF), 2021)
Failure of small businesses many times is because of poor implementation of long-term financial strategies. Women small business owners face many challenges in financing their small businesses because they may not have a financial plan. Interviews with 11 women small business owners in Cleveland County, North Carolina were completed to discuss ways to fund and sustain their small business. The success of women small business owners can strengthen the local economy by stimulating economic growth, increase the quality of life for the owner and their family, and can improve the standard of living in their community.
Keywords: M13; L26; M21; 650; Financial; women; entrepreneurship; small business